TAHLIL AKHTHO’ AN-NABR WA TANGHIM FI MUHADATSATI AL-THOLABAH AL-YAUMIYAH BI AL-LUGHAH AL-ARABIYAH: تحليل أخطاء النبر والتنغيم في محادثة الطلبة اليومية باللغة العربية - Syafni, Hafidhah (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2023)
Arabic requires proficiency in voice stress and intonation in conversation, but most students do not pay attention to this area and they are mistaken in the delivery of a sentence so that it makes a misunderstanding in comprehending the meaning of the conversation, which is why this discussion is proposed. The purpose of this article is to find out how students use voice stress and intonation in daily Arabic conversations, what mistakes occur during conversations, especially in the themes of "holidays" and "train stations" and what causes the mistakes to occur, and to get solutions so that students can use voice stress and intonation properly. The method of this article is descriptive with a qualitative approach which is a research method that utilises qualitative data and is described descriptively and in analysing it, Miles and Huberman's theory was used. The result of this study is that the 10th grade students' use of voice stress and intonation is weak, even some of them cannot distinguish between question sentences and other sentences. Many mistakes occur in question sentences and ordinary statement sentences, this is due to their lack of knowledge of the meaning of vocabularies, the lack of desire of students to speak with correct language, the small number of organization members, especially the language section, and inadequate media technology. The solutions to these problems are the holding of vocabulary classes, language conversation activities in the afternoon, frequent opening of dictionaries, and punishment for violators of language rules.